The cult of pharmacology : how America became the world's most troubled drug culture - DeGrandpre, Richard J. (e-Duke books scholarly collection., 2006)
Richard DeGrandpre, author of Ritalin Nation, targets the illogic underlying U.S. drug policy and Americans' limited understanding of what drugs are and how they work.